My first numbers let's get counting! - Sirett, Dawn; Appleton, Polly; Calver, Susan; Ganguly, Srijani; Hunt, Rachael Parfitt (London dorling kindersley, 2024)
Let's have fun counting to 10, then up to 20, recognising numbers, and saying lots of words! 1 toy train, 2 little feet, 3 spotty ladybirds - it's time to get counting! Babies and toddlers will love joining in and learning their numbers from 1 to 10, and then up to 20 in this first counting book that's perfect for sharing
Arithmetic notions
Keywords: Mathematics